2015
DOI: 10.1038/mp.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment in aged primates is associated with region-specific network dysfunction

Abstract: Age-related deficits in episodic memory result, in part, from declines in the integrity of medial temporal lobe structures, such as the hippocampus, but are not thought to be due to widespread loss of principal neurons. Studies in rodents suggest, however, that inhibitory interneurons may be particularly vulnerable in advanced age. Optimal encoding and retrieval of information depend on a balance of excitatory and inhibitory transmission. It is not known whether a disruption of this balance is observed in agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
88
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 45 publications
14
88
0
Order By: Relevance
“…Interestingly, the idea that a net shift towards inhibition may be associated with impaired cognitive performance may not hold true for all brain areas. Consider that GABA B R expression during aging is more preserved in hippocampus than in PFC (Banuelos, et al, 2014, Beas, et al, 2016, McQuail, et al, 2012, McQuail, et al, 2015), that aged hippocampal pyramidal cells are likely subject to reduced dendritic inhibition associated with reduced numbers of inhibitory interneurons (Bakker, et al, 2012, Spiegel, et al, 2013, Stanley, et al, 2012, Thome, et al, 2015), and that some mouse models of Alzheimer’s are associated with increased hippocampal excitability (Davis, et al, 2014, Hall, et al, 2015, Palop, et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the idea that a net shift towards inhibition may be associated with impaired cognitive performance may not hold true for all brain areas. Consider that GABA B R expression during aging is more preserved in hippocampus than in PFC (Banuelos, et al, 2014, Beas, et al, 2016, McQuail, et al, 2012, McQuail, et al, 2015), that aged hippocampal pyramidal cells are likely subject to reduced dendritic inhibition associated with reduced numbers of inhibitory interneurons (Bakker, et al, 2012, Spiegel, et al, 2013, Stanley, et al, 2012, Thome, et al, 2015), and that some mouse models of Alzheimer’s are associated with increased hippocampal excitability (Davis, et al, 2014, Hall, et al, 2015, Palop, et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…These inhibitory neurons expressing PV and SOM, among the most affected populations impacted by aging in the hippocampus (26,27,31,59,60), have been shown to play important roles in learning and memory operations (28)(29)(30)(31)61). As our memory-guided learning task plausibly engages hippocampal processes, the positive changes recorded in inhibitory neuronal populations presumably reflect the fact that our simple form of training has induced physical and functional changes that have had positive, generalized impacts expressed very broadly across forebrain networks.…”
Section: Discussionmentioning
confidence: 99%
“…Aging itself can be associated with limited memory impairment not only in elderly humans but also in many other species that do not develop Alzheimer’s disease (AD). Memory impairment in aged laboratory animals, including both rodents and non-human primates, is associated with increased neural activity in specific circuits within the hippocampal memory system (Thomé et al, 2016; Wilson et al, 2005; Simkin et al, 2015). Mounting evidence from basic science and clinical studies has also demonstrated that neuronal circuits become hyperactive particularly in early stages of AD (Busche et al, 2012; Busche and Konnerth, 2015).…”
Section: Introductionmentioning
confidence: 99%